Do the "smart kids" catch up? Technological capabilities, globalisation and economic growth - Claudius Gräbner; Philipp Heimberger; Jakob Kapeller (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2020)
This paper analyses the impact of technological capabilities on convergence. While looking at the relevance of differences in technological capabilities has a long tradition in economics when it comes to explaining persistent deviations in income, we provide econometric tests on the role of technology in determining convergence outcomes in a growth regression framework. We exploit recent advances in measuring technological capabilities for a global country sample over the period 1985-2014. Our results show that convergence is conditional on technological capabilities. This finding is robust to controlling for economic globalisation, resource dependence, institutional quality and other confounding factors. The initial stock of accumulated technological capabilities is one essential factor that may allow poorer countries to convergence towards higher income levels in rich countries. A successful catching-up process cannot be expected for countries lacking a sufficient stock of previously accumulated technological capabilities.
Keywords: E6; F4; O3; 330; Economic complexity; technology; convergence; catch-up; globalisation; openness